How are global value chains altering policy narratives? - Carlo Pietrobelli; Roberta Rabellotti; Ari Van Assche (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
Global value chains (GVCs) have taken the policy world by storm, with many policymakers viewing them as potent tools to boost economic development through industrial upgrading. In this Perspective, the authors argue that zooming in on the roles of tasks, linkages and firms helps clarify the novelty of GVC-oriented policies.
Keywords: 330